2017
DOI: 10.1002/2017jd027266
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Potential Photochemical Roles of Formaldehyde in an Urban Atmosphere in South China

Abstract: Formaldehyde (HCHO) is an important intermediate in tropospheric photochemistry. However, study of its evolution characteristics under heavy pollution conditions in China is limited, especially for high temporal resolutions, making it difficult to analyze its sources and environmental impacts. In this study, ambient levels of HCHO were monitored using a proton‐transfer reaction mass spectrometer at an urban site in the Pearl River Delta of China. Continuous monitoring campaigns were conducted in the spring, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 105 publications
(217 reference statements)
2
28
0
2
Order By: Relevance
“…In addition to autumn, Ling et al (2017) showed strong photochemical activities in summer, but the prevailing southerly and southeasterly winds from the oceans alleviated carbonyls pollution during summer, whereas the northeasterly winds in autumn aggravated the pollution. Wang et al (2017a) investigated the source category contributions to HCHO in different seasons. They used the photochemical age-based parameterization method and found that the contributions of biogenic sources (including both primary and secondary biogenic sources) to HCHO were much higher during summer (41%) and autumn (39%) than during spring (26%) and winter (28%).…”
Section: Pearl River Deltamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to autumn, Ling et al (2017) showed strong photochemical activities in summer, but the prevailing southerly and southeasterly winds from the oceans alleviated carbonyls pollution during summer, whereas the northeasterly winds in autumn aggravated the pollution. Wang et al (2017a) investigated the source category contributions to HCHO in different seasons. They used the photochemical age-based parameterization method and found that the contributions of biogenic sources (including both primary and secondary biogenic sources) to HCHO were much higher during summer (41%) and autumn (39%) than during spring (26%) and winter (28%).…”
Section: Pearl River Deltamentioning
confidence: 99%
“…The collected data show that various aspects of carbonyls have been investigated. Analyses of the temporal and spatial distributions of carbonyls have been widely performed (Cheng et al, 2014;Dai et al, 2012;Guo et al, 2016;Ho et al, 2014a;Ho et al, 2015;Lui et al, 2017a;Lui et al, 2017c;Pang and Lee, 2010;Pang and Mu, 2006), but few studies have focused on the sources or photochemical mechanisms of carbonyls, or their influence on atmospheric chemistry, air quality, and human health (Ling et al, 2017;Liu et al, 2009;Wang et al, 2017a;Xue et al, 2016;Yang et al, 2018), so these aspects are relatively poorly understood. In addition, most studies have focused on the characteristics of gaseous carbonyls; observational data on high-molecular weight carbonyls are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…HCHO usually originates from the photochemical reactions of volatile organic compounds (VOCs) and can be used as a proxy for the total reactivity of VOCs 3 . The sources of VOCs include fire, vegetation and anthropogenic emissions 4 . VOCs are important precursors of secondary organic aerosols and ozone (O 3 ) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…larger than direct emissions of HCHO, and will occur a few hours after the peak commuter time (e.g. Lin et al (2012); Wang et al (2017)). The early morning rush hour in Delhi starts after 0700 so we expect a 0930 overpass to also capture some fraction of the secondary HCHO production.…”
Section: Anthropogenic Hotspotsmentioning
confidence: 99%